KORELASI TINGKAT PENGHINDARAN RISIKO DENGAN ECONOMIC WELLBEING PETANI PADI - Yanuarti, Rizky; Ibanah, Indah; Lutfiyah, Lenny; Mutmainah, Laily; Suwandari, Anik; Rokhani, Rokhani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2022)
Farmers' attitudes and perspectives towards risk will be reflected in their decision-making and will be related to risk aversion levels. Recognizing farmers' attitudes towards risk will be beneficial in providing innovative product development according to farmers' needs. The development of a farmer protection system against risks has been carried out by the Indonesian government in the form of Rice Farming Insurance (AUTP). This study aims to analyze risk aversion level (RAL) and measure its relationship to farmers' economic well-being which is illustrated by the income of rice farmers in Wuluhan, Jember Regency. Multiple price list designs were used to analyze RAL and Pearson analysis was employed to measure their correlation. The results showed that farmers tend to show a relatively high level of risk aversion, in which 36.923% of farmers prefer to insure their entire land (option A). Meanwhile, only 2.308% prefer not to insure their land (option F). Pearson correlation value is 0.69, it can be interpreted that an increase in income will be followed by an increase in the RAL value meaning that the level of risk aversion decreases. The research results are useful for policymakers, especially risk in the agricultural sector to determine innovation in optimizing the implementation of AUTP